2020
DOI: 10.3390/md18020116
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthinol from the Diatom Nitzschia Laevis Ameliorates Neuroinflammatory Responses in Lipopolysaccharide-Stimulated BV-2 Microglia

Abstract: In recent years, microalgae have drawn increasing attention as a valuable source of functional food ingredients. Intriguingly, Nitzschia laevis is rich in fucoxanthinol that is seldom found in natural sources. Fucoxanthinol, a marine xanthophyll carotenoid, possesses various beneficial bioactivities. Nevertheless, it's not clear whether fucoxanthinol could exert anti-neuroinflammatory function. In light of these premises, the aim of the present study was to investigate the anti-inflammatory role of fucoxanthin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Earlier studies suggested that DOX causes inflammatory reactions in the vasculature and myocardium and elevates the concentrations of proinflammatory cytokines (e.g., TNF- α , IL-1 β , and IL-2) [ 50 ]. A critical target for anti-inflammatory action is the Nrf2/HO-1 signaling pathway [ 51 ]. In this study, DOX exposure provoked a host of proinflammatory factors, such as TNF- α , IL-1 β , and IL-6; however, the inflammatory reaction was blunted by choline treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies suggested that DOX causes inflammatory reactions in the vasculature and myocardium and elevates the concentrations of proinflammatory cytokines (e.g., TNF- α , IL-1 β , and IL-2) [ 50 ]. A critical target for anti-inflammatory action is the Nrf2/HO-1 signaling pathway [ 51 ]. In this study, DOX exposure provoked a host of proinflammatory factors, such as TNF- α , IL-1 β , and IL-6; however, the inflammatory reaction was blunted by choline treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Fucoxanthinol is a major gastrointestinal metabolite of dietary fucoxanthin, and to date, the number of natural sources of this compound is reduced, including, for example, the diatom Nitzschia laevis [ 122 , 123 ]. Fucoxanthinol also plays essential roles in the regulation of obesity, and displays relevant health promoting properties, such as antidiabetic, anti-tumoral and anti-inflammatory [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…65 Fucoxanthinol, a carotenoid isolated from Nitzschia laevis protects against neuroinflammatory response in BV-2 microglia. 66 Terpenoids extracted from other S. platensis strains have also been reported for its neuroprotective activities against oxidative stress. 67,68 According to our results, organic solvent extracts showed stronger antioxidant activities than water extract.…”
Section: Discussionmentioning
confidence: 99%